EBRD financing in Kosovo (2013-2020): Impact and strategies - Albrim Badallaj (Economics, Management and Sustainability)
Purpose: This paper analyzes the European Bank for Reconstruction and Development's (EBRD) strategic financing roles in Kosovo from 2013 to 2020, focusing on economic impacts and developmental progress. Methodology: Employing a quantitative and comparative approach, this study utilizes secondary data analysis, supported by statistical tools in Microsoft Excel, to evaluate the effectiveness of EBRD investments in various sectors within Kosovo. Results: The findings reveal significant EBRD investments, primarily in SMEs and infrastructure, contributing to competitive gains and sustainable development. The study details the volume of investments and their distribution across different sectors, highlighting substantial impacts on employment and green energy initiatives. Theoretical Contribution: This research enriches the literature on international financial institutions' roles in post-conflict economic development, providing a nuanced understanding of the EBRD's strategic priorities and operational outcomes in transitional economies. Practical Implications: The study offers policymakers and development agencies insights into practical strategies for leveraging international finance for economic growth and sustainability. Recommendations are provided to enhance the focus on renewable energy and infrastructure, aligning with global sustainable development goals.